THE ADVANTAGES OF USING MODERN PEDAGOGICAL TECHNOLOGIES IN TEACHING FOREIGN LANGUAGE CULTURE (Sciental Journal of Education Humanities and Social Sciences, 2026)
The present article presents the analysis of the advantages of using modern pedagogical technologies in the process of teaching foreign language, speech etiquette in it, enriching vocabulary and developing speaking skills. The article demonstrates the most popular technologies used in teaching process.